(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To evaluate 12-month clinical outcomes of a treat-and-extend regimen with intravitreal aflibercept injections in patients with occult (type 1) choroidal neovascularization (CNV) secondary to chronic central serous chorioretinopathy (CSC). Methods: This was a prospective observational single-center study involving 24 patients (24 eyes) with occult (type 1) CNV secondary to chronic CSC. All patients received three initial loading doses of intravitreal 2 mg (0.05 ml) aflibercept at 4-weekly intervals, followed by a treat-and-extend protocol. The primary outcome was best-corrected visual acuity (BCVA) at 12 months. Statistical analyses were conducted and graphs were created using Statistica 10.0 software. Results: Mean BCVA increased significantly from 0.44 ± 0.35 at baseline to 0.58 ± 0.3 at month 12 (р = 0.01). At month 12, complete resolution of SRF was observed in 18 eyes (75%). The mean number of intravitreal aflibercept injections over 12 months was 7.5 ± 1.4. Conclusion: Treat-and-extend intravitreal aflibercept is an effective and safe approach for managing patients with occult (type 1) CNV secondary to chronic CSC.